Astaxanthin absorption modulated antioxidant enzyme activity and targeted specific metabolic pathways in rats. (6th July 2022) - Jia, Zhe; Song, Ru; Xu, Yan; Liu, Xinyan; Zhang, Xiaoxia
Abstract: BACKGROUND: Saponification contributed to an increase in the in vitro antioxidant activity of astaxanthin (Asta) extracts derived from Penaeus sinensis ( Solenocera crassicornis ) by‐products. However, the influence of non‐saponification (N‐Asta) and saponification Asta (S‐Asta) absorption on antioxidant activity in vivo was limited. The antioxidant properties of N‐Asta and S‐Asta were therefore compared in Sprague Dawley male rats after 6 h and 12 of absorption using biochemistry assays combined with an untargeted metabonomics strategy. RESULTS: Non‐saponified Asta and S‐Asta showed similar digestive properties in a stimulated gastrointestinal tract. Increased glutathione content and decreased malondialdehyde content were measured in the liver tissues of N‐Asta and S‐Asta treated rats after 12 h of absorption. Absorption of N‐Asta increased liver total superoxide dismutase, glutathione peroxidase, and catalase activity. Treatment with S‐Asta up‐regulated NAD(P)H: quinine oxidoreductase‐1, and heme oxygenase‐1 expression was associated with the nuclear erythroid 2‐related factor 2/antioxidant responsive element pathway at the end of 12 h absorption. With partial least square‐discriminant analysis and metabolite heatmap profiles, the S‐Asta group was clearly separated from the N‐Asta group. The S‐Asta treatment also demonstrated stronger influences on plasma metabolites than the N‐Asta treatment. Both N‐Asta and S‐Asta absorption showed critical roles in the regulation of specific metabolites, and 15 potential biomarkers were identified in eight key pathways to separate these experimental groups after 12 h of absorption. However, an increased serotonin level was only detected in the S‐Asta group after 12 h absorption. CONCLUSION: Absorption of N‐Asta and S‐Asta induced different antioxidant effects in normal rats, which were associated with metabolite changes. © 2022 Society of Chemical Industry.